1976
DOI: 10.1073/pnas.73.11.4225
|View full text |Cite
|
Sign up to set email alerts
|

Chemical transmission between rat sympathetic neurons and cardiac myocytes developing in microcultures: evidence for cholinergic, adrenergic, and dual-function neurons.

Abstract: Electrophysiological studies were made on microcultures (300-500 Ism in diameter) in which solitary sympathetic principal neurons from newborn rats grew on previously dissociated rat heart cells. (1,6,7,8). In contrast, when the neurons are cultured in the presence of nonneuronal cells (e.g., from ganglia or heart), or in medium conditioned by such cells, the neuronal population synthesizes both AcCh and NE (2, 9), and many neurons form nicotinic cholinergic synapses on each other (6-8, 10, 11). These effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
175
1

Year Published

1978
1978
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 341 publications
(181 citation statements)
references
References 20 publications
5
175
1
Order By: Relevance
“…Sympathetic neurons dissociated from the superior cervical ganglia of newborn rats and grown for several weeks in the culture' conditions used in the present experiments synthesize, store, and release norepinephrine (18,19,20). Single sympathetic neurons grown in microcultures have been shown with physiological techniques to secrete norepinephrine onto cardiac myocytes (12), and the same neurons are found to contain vesicles with granular deposits in synaptic varicosities after permanganate fixation (17). The present study has demonstrated that some of the vesicles in the growth cones of these dissociated adrenergic neurons contain dense granules after permanganate fixation.…”
Section: Discussionmentioning
confidence: 91%
“…Sympathetic neurons dissociated from the superior cervical ganglia of newborn rats and grown for several weeks in the culture' conditions used in the present experiments synthesize, store, and release norepinephrine (18,19,20). Single sympathetic neurons grown in microcultures have been shown with physiological techniques to secrete norepinephrine onto cardiac myocytes (12), and the same neurons are found to contain vesicles with granular deposits in synaptic varicosities after permanganate fixation (17). The present study has demonstrated that some of the vesicles in the growth cones of these dissociated adrenergic neurons contain dense granules after permanganate fixation.…”
Section: Discussionmentioning
confidence: 91%
“…How sympathetic fibers with an adrenergic phenotype restore cholinergic function in hippocampus is unknown. A small percentage (Ͻ1%) of SCG neurons are cholinergic (Schafer et al, 1998), and sympathetic neurons, including those in the SCG, are capable of gaining a cholinergic phenotype or switching their phenotype altogether from adrenergic to cholinergic (Furshpan et al, 1976;Potter et al, 1981;Landis and Keefe, 1983;Wolinsky and Patterson, 1983;Schafer et al, 1997Schafer et al, , 1998Francis and Landis, 1999;Yang et al, 2002;Weihe et al, 2005). Therefore, we entertained the possibility that sprouting from the SCG might restore cholinergic function, and thus mLTD expression, by replacing lost central cholinergic innervation to hippocampus, potentially by any one, or all, of these mechanisms.…”
Section: Increased Cholinergic Innervation Is Seen In Animals With Symentioning
confidence: 97%
“…However, the rapid loss of these fibers, which occurs within 5-7 d after unilateral ganglionectomy performed at a time when reinnervation is well established, strongly suggests that the SCG is directly responsible for, and likely the source of, the cholinergic reinnervation. Sympathetic neurons, including those in the SCG, have the unique ability to gain a cholinergic phenotype and/or functionally alter their phenotype from adrenergic to cholinergic (Furshpan et al, 1976;Potter et al, 1981;Landis and Keefe, 1983;Wolinsky and Patterson, 1983;Schafer et al, 1997Schafer et al, , 1998Francis and Landis, 1999;Yang et al, 2002;Weihe et al, 2005). Thus, the VAChT-positive fibers in hippocampus may arise from a gain of cholinergic function or an adrenergic to cholinergic phenotype switch.…”
Section: Source Of the Vacht-positive Fibersmentioning
confidence: 99%
“…Therefore, if both of these vesicles are synaptic vesicles, the transmitter substance of the cell might not only be GABA. Among tissue-cultured rat sympathetic neurones, there were some which released both ACh and norepinephrine (Furshpan, MacLeish, O'Lague & Potter, 1976). Multiple transmitter substances in a neurone were also suggested in molluscs (Brownstein, Saavedra, Axelrod, Zeman & Carpenter, 1974;Cottrell, 1976).…”
Section: Transmitter Substance(s) Of the Photoreceptormentioning
confidence: 97%